Influência das épocas do ano na morfometria testicular e epididimária, características do sêmen e proteínas do sêmen em SDS-PAGE em zebus e taurinos - Mungai Chacur, Marcelo George; Archanjo dos Reis, Juliana Domingos; Tavares, Lucas Silva; Sanches, Klisman; Guaberto, Luciana; Alves, Vagner Camarini; Oba, Eunice [UNESP]; Ramos, Alcides Amorim [UNESP] (Univ Fed Rio Grande do Sul, 2014)
Background: Seminal plasma is a set of secretions from accessory male reproduction organs which influence spermatic functions. Climate changes that affect gametogenesis may produce low reproduction efficiency in bulls. Electrophoresis is a great help in the diagnosis of reproduction pathologies and in animal differentiation with regard to fertility within the context of climate changes. Current research aims at studying the influence of the rainy and dry periods in testicle and epididymis morphometry, semen characteristics and protein of seminal plasma by SDS-PAGE electrophoresis in extensively bred Nellore and Simental bulls.Materials, Methods & Results: Five Nellore and two Simental bulls, at mean age of four years, were employed. Semen collection was undertaken during the rainy (spring and summer) and dry (autumn and winter) at 15-day intervals. One hundred and fifty-four ejaculations were analyzed and scrotal, testicle and epididymis measurement was provided. Samples of semen plasma were centrifuged and conditioned at -196 degrees C till electrophoresis processing. Proteins were extracted from 200 mu L from each sample in an extraction buffer composed of 0.625 M Tris -HCl, pH 6.8; 2% SDS, 5% beta -mercaptoethanol and 20% glycerol. Proteins were quantified and electrophoreses processed. Data were evaluated by analysis of variance and means compared by Tukey's test at 5%. The expression TV = 0.0396 x (average testicle length) x (scrotal perimeter) 2 was used for testicle volume (TV), with TV = 460.14 cm(3) for the Simental breed during the rainy season and TV = 571.26 cm(3) during the dry season. Nellore bulls showed TV = 524.75 cm(3) during the rainy season and 515.13 cm(3) during the dry season. TV increased in Simental bulls during the dry period, whereas Nellore breed increased during the rainy one. There was an increase (P < 0.05) in big and total defects during the rainy season for both breeds. Further, 30 kDa in the seminal plasma occurred in all samples for both breeds and seasons under analysis. Band 179 kDa occurred in 43% and 14% of samples from Nellore and Simental breeds respectively. Molecular weights of identified bands in the gels varied between 4 and 205 kDa.Discussion: Testicle length axis varied significantly between breeds at specific seasons. Variation may be due to adaptation and anatomic plasticity of the testicles within specific seasons of the year under analysis. TV rise in Simental bulls during the dry period may have contributed towards the decrease of minor and major spermatic defects with an improvement of semen quality. Spermatic motility during the dry period and total spermatic defects during the rainy season for Simental breed provided fall in semen quality. Morphological abnormalities of spermatozoa are lower in the dry season. Season affects testicle morphometry and protein composition of the bulls' seminal plasma. Protein band 179 kDa occurred in Nellore bulls during the two analyzed seasons, a fact that has not been described in the literature.
Influence of Year Periods on Testicle and Epididymal Morphometry, Semen Characteristics and Seminal Proteins by SDS-PAGE in Zebu and Taurine
Keywords: bulls; sazonality; semen; seminal plasma proteins